Functions of MiRNA-128 on the Regulation of Head and Neck Squamous Cell Carcinoma Growth and Apoptosis - Hauser, Belinda (PLoS One, 2015)
BACKGROUND: Incidence of head and neck squamous cell carcinoma (HNSCC) has continuously increased in past years while its survival rate has not been significantly improved. There is a critical need to better understand the genetic regulation of HNSCC tumorigenesis and progression. In this study, we comprehensively analyzed the function of miRNA-128 (miR-128) in the regulation of HNSCC growth and its putative targets in vitro and in vivo systems. METHODS: The function and targets of miR-128 were investigated in human HNSCC cell lines (JHU-13 and JHU-22), which were stably transfected with the miR-128 gene using a lentiviral delivery system. The expression levels of miR-128 and its targeted proteins were analyzed with qRT-PCR, Western blotting and flow cytometry. The binding capacity of miRNA-128 to its putative targets was determined using a luciferase report assay. MTT, colony formation, and a tumor xenograft model further evaluated the effects of miR-128 on HNSCC growth. RESULTS: We generated two miR-128 stably transfected human HNSCC cell lines (JHU-13(miR-128) and JHU-22(miR-128)). Enforced expression of miR-128 was detected in both cultured JHU-13(miR-128) and JHU-22(miR-128) cell lines, approximately seventeen to twenty folds higher than in vector control cell lines. miRNA-128 was able to bind with the 3′-untranslated regions of BMI-1, BAG-2, BAX, H3f3b, and Paip2 mRNAs, resulting in significant reduction of the targeted protein levels. We found that upregulated miR-128 expression significantly inhibited both JHU-13(miR-128) and JHU-22(miR-128) cell viability approximately 20 to 40%, and the JHU-22(miR-128) tumor xenograft growth compared to the vector control groups. CONCLUSIONS: miR-128 acted as a tumor suppressor inhibiting the HNSCC growth by directly mediating the expression of putative targets. Our results provide a better understanding of miRNA-128 function and its potential targets, which may be valuable for developing novel diagnostic markers and targeted therapy.